THE EFFECT OF BRAND EXPERIENCE ON BRAND LOYALTY WITH THE MEDIATION OF BRAND TRUST AND BRAND SATISFACTION OF THE IPHONE APPLE BRAND IN JABODETABEK - Jennifer Chandra; Pauline Henriette P. Tan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2023)
In era of globalization, the geographical boundaries that used to separate one country from another no longer serve as obstacles to communicating or engaging with one another. This is supported by the availability of smartphones that employ highly advanced technology. This research aims to examine the impact of brand experience on brand loyalty via brand satisfaction and brand trust as a mediator. The object of this research is a foreign technological brand, namely Apple, and specifically its smartphone product, the iPhone. The research contribution for this research is Apple brands and those included in the international business scope will be able to continue to provide the best brand experience to retain their customers by stabilizing the quality of their goods and services. This study employed a quantitative methodology based on questionnaires. Researchers disseminate questionnaires using Instagram, WhatsApp, and LINE for personal dissemination. This research was carried out in Indonesia, specifically in Jabodetabek area. There were 209 respondents for the actual test. Using the outer model and inner model, Smart-PLS 3.2.9 is utilized to analyse data. The outer model comprises validity and reliability tests, whereas the inner model uses R-square, T-statistics, Original Samples, and P-square to analyse the relationship between variables. Based on the results obtained, researchers can conclude that Brand Experience, Brand Satisfaction, Brand Trust and Brand Loyalty have a significant positive relationship, with Brand Satisfaction and Brand Trust as mediators between Brand Experience and Brand Loyalty.